Analysing collocational patterns of semi-technical words in science textbooks - Menon, Sujatha; Mukundan, Jayakaran (Universiti Putra Malaysia Press, 2010)
This paper analyses the discourse of science through the study of collocational patterns of semi-technical words in science textbooks used by upper secondary students in Malaysia. Semi-technical vocabulary is considered to be one of the most problematic lexical areas for second language learners learning science in English, as these words usually take on extended meanings in technical contexts. The study explores the collocational and colligational patterns of semi-technical words in a corpus of 12 science textbooks. The analysis found some common lexical and grammatical patterns which seemed to share similar aspects of meaning and also showed that collocations of semi-technical words often form compounds with extended and more genre specific meanings. Thus, it is important to focus on some sense and grammar patterns as students need to understand why even though many of these collocations share similar syntactic characteristics, the flexibility of some combinations are arbitrarily blocked by usage.